Patterns in Bathyal Demersal Biodiversity and Community Composition Around Archipelagos in the Tropical Eastern Pacific - Giddens, Jonatha; Goodell, Whitney; Friedlander, Alan; Salinas-de-León, Pelayo; Shepard, Charles; Henning, Brad; Berkenpas, Eric; Sala, Enric; Turchik, Alan (Frontiers in Marine Science, 2019)
Deep-sea fauna of the Tropical Eastern Pacific (TEP) have remained largely un-described because exploration has historically been a challenge in these remote locations. Consequently, little is currently known about deep-ocean biodiversity in the TEP. An enriched understanding of biogeographic patterns and the factors that influence them is crucial to the success of efforts to conserve deep-sea communities. The objectives of this research were to provide the first assessment of biodiversity and community composition of bathyal demersal (200 - 3,000m) fauna across multiple ocean/island archipelagos in the TEP. To better understand biodiversity and its drivers in the region, we tested the hypotheses that biodiversity and faunal assemblage composition vary with location and environmental drivers (e.g bathymetry, oxygen concentration). Using Deep-Ocean Dropcams, we collected video footage from Clipperton, Galápagos, Revillagigedos, and Malpelo, in depths ranging from 200 to 3,000 m. Taxa richness, Shannon diversity, and Simpson diversity were calculated for each location. In general, biodiversity values were high closer to the equator and closer to the continent, and low in the locations farther north and farther west. Fish family biodiversity was highest in the Galápagos, followed by Malpelo. In contrast, Clipperton had significantly lower fish family richness compared to all other locations. For invertebrate orders, the Revillagigedos were significantly lower in biodiversity compared to the Galápagos and Malpelo. Broad-scale Bathymetric Position Index (BPI) and dissolved oxygen had a positive effect on fish diversity metrics. Both fish and invertebrate assemblages were significantly different among locations. Around each of the island groups are vastly different current patterns, which likely accounts for some of the variation we observed in biodiversity and community composition. Due to the longitudinal East Pacific Rise, which limits population connectivity by creating a spatial barrier to gene flow and dispersal among marine organisms, the TEP is largely isolated from the wider Pacific. The islands and archipelagos likely represent important stepping-stones and corridors for species connectivity across the TEP and the wider Pacific. Therefore, the preservation of these intact ecosystems is crucial for maintaining biodiversity both within the TEP as well as across the wider Pacific region.